2002
DOI: 10.1523/jneurosci.22-19-08653.2002
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the Tegmental Pedunculopontine Nucleus Block the Rewarding Effects and Reveal the Aversive Effects of Nicotine in the Ventral Tegmental Area

Abstract: Nicotine, the primary psychoactive component of tobacco smoke, is known to possess potent rewarding and aversive stimulus properties. The mammalian ventral tegmental area (VTA) is involved importantly in the mediation of the motivational effects of nicotine. However, the neural outputs from the VTA that may be involved in the transmission of the rewarding and aversive motivational effects of nicotine are not well understood. We report that bilateral lesions of the tegmental pedunculopontine nucleus (TPP) doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 41 publications
8
69
1
Order By: Relevance
“…The aversive a-process is DA mediated in both acute opiate (Zito et al, 1988) and acute nicotine motivation, as shown presently. The rewarding a-process for acute opiates and acute nicotine are TPP mediated (Laviolette et al, 2002). We have shown that the rewarding b-process for acute nicotine is not DA mediated, which resembles the DA-independent acute aversive b-process for opiates .…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The aversive a-process is DA mediated in both acute opiate (Zito et al, 1988) and acute nicotine motivation, as shown presently. The rewarding a-process for acute opiates and acute nicotine are TPP mediated (Laviolette et al, 2002). We have shown that the rewarding b-process for acute nicotine is not DA mediated, which resembles the DA-independent acute aversive b-process for opiates .…”
Section: Discussionmentioning
confidence: 71%
“…Although the TPP appears to be a good candidate to mediate the acute b-process in both nicotine and opiate motivation, it was recently suggested that the TPP does not mediate the acute opiate b-process (Vargas-Perez et al, 2009). However, TPP involvement in the acute nicotine b-process cannot be completely ruled out as the acute nicotine b-process is rewarding and TPP involvement in acute nicotine reward has been previously demonstrated (Laviolette et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, these data are consistent with the hypothesis that nicotine-induced amplification of brain reward activity provides an important source of motivation that supports the initiation and maintenance of nicotine selfadministration in rats (Kenny and Markou, 2006), and perhaps the tobacco-smoking habit in humans (Donny et al, 2003;Kenny, 2007). On the basis of our observation that NMDA receptor blockade reversed the valence of nicotine's actions on reward circuitries, we may speculate that NMDA receptor antagonism decreased nicotine intake by rendering rats less sensitive to the appetitive effects of nicotine and more sensitive to its aversive effects (see Laviolette et al, 2002;Laviolette and van der Kooy, 2003). Such an interpretation would account for the fact that rats did not display compensatory increases in their nicotine intake after LY235959 treatment similar to those observed in cocaine or amphetamine self-administering rats treated with doses of dopamine receptor antagonists that attenuate the rewarding effects of these drugs (Yokel and Wise, 1975;Koob et al, 1987).…”
Section: Reward-enhancing and Reinforcing Effects Of Nicotine Requirementioning
confidence: 87%
“…We expected to see greater neural activity to smoking cues in the areas of the pedunculopontine nucleus, ventral tegmental area, and ventral striatum, the proposed pathway through which nicotine and associated cues modulate the mesolimbic dopaminergic system (Corrigall et al, 1994;Laviolette et al, 2002). Further, we hypothesized greater perfusion in the ventral striatum and the interconnected amygdala, anterior and posterior cingulate, select prefrontal regions, hippocampus, and thalamus as these regions are implicated in modulating behavioral responses to drug-related stimuli (Brody et al, 2002;Childress et al, 1999; Franklin and Druhan, 2000a, b;Grant et al, 1996;Wang et al, 1999).…”
Section: A Priori Cns Regions Of Interestmentioning
confidence: 99%